Treatment of Organophosphate Poisoning with Experimental Oximes: A Review - Lorke, Dietrich E.; Petroianu, Georg A. (Current Organic Chemistry, 2019)
Standard therapy of Organophosphorus Compound (OPC) poisoning with oxime-type acetylcholinesterase (AChE) reactivators is unsatisfactory. New bispyridinium oximes have therefore been synthesized. This review summarizes in vitro characteristics of established (pralidoxime, obidoxime, trimedoxime, HI-6) and experimental (K-)oximes, and compares their protective efficacy in vivo, when administered shortly after exposure to Diisopropylfluorophosphate (DFP) and three OPC pesticides (ethyl-paraoxon, methylparaoxon, azinphos-methyl) in the same experimental setting. In addition to reactivating cholinesterase, oximes also inhibit this enzyme; strongest AChE inhibition (IC50 rat blood: 1-9 μM) is observed in vitro for the oximes with a xylene linker (K-107, K-108, K-113). AChE inhibition is weakest for K-27, K-48 and HI-6 (IC50 >500 μM). Intrinsic AChE inhibition of oximes in vitro (IC50, rat) is strongly correlated with their LD50 (rat): oximes with a high IC50 (K-27, K-48, pralidoxime, obidoxime) also show a high LD50, making them relatively non-toxic, whereas oximes K-107, K-108 and K-113 (low IC50 and LD50) are far more toxic. When given in vivo after OP exposure, best protection is conferred by K-27, reducing the relative risk of death to 16-58% of controls, which is significantly superior to pralidoxime in DFP-, ethyl-paraoxon- and methylparaoxon- exposure, and to obidoxime in ethyl-paraoxon- and methyl-paraoxon-exposure. Marked reduction in mortality is also achieved by K-48, K-53, K-74 and K-75, whereas K-107, K-108 and K-113 have no or only a very weak mortality-reducing effect. K-27 is the most promising K-oxime due to its strong reactivation potency, weak cholinesterase inhibition and high LD50, allowing administration in large, very efficacious dosages.
Keywords: cox analysis